2015
DOI: 10.3233/jpi-120359
|View full text |Cite
|
Sign up to set email alerts
|

Use of daptomycin in neonates: A case report and review of the literature

Abstract: We report a case of persistent bacteremia secondary to methicillin-resistant S. aureus (MRSA) in a preterm neonate successfully treated with daptomycin. Although the MRSA isolate was susceptible to vancomycin, there was no clinical or microbiologic response. Within 3 days of therapy with daptomycin, clinical improvement was noted, along with sterilization of blood cultures. Little data exist on neonatal pharmacokinetics of daptomycin. This report highlights the potential advantage that daptomycin offers in tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[1][2][3] The cyclic lipopeptide daptomycin has a unique mechanism of action that disrupts bacterial membrane function, leading to rapid killing of Gram-positive bacteria. 3,5,6 Pharmacokinetic (PK) studies of daptomycin have been reported in infants <120 days of age with suspected Gram-positive infection 7 and in pediatric patients 2-17 years of age with proven or suspected Gram-positive infection, 8,9 but not in infants 3-24 months of age. 3,5,6 Pharmacokinetic (PK) studies of daptomycin have been reported in infants <120 days of age with suspected Gram-positive infection 7 and in pediatric patients 2-17 years of age with proven or suspected Gram-positive infection, 8,9 but not in infants 3-24 months of age.…”
mentioning
confidence: 99%
“…[1][2][3] The cyclic lipopeptide daptomycin has a unique mechanism of action that disrupts bacterial membrane function, leading to rapid killing of Gram-positive bacteria. 3,5,6 Pharmacokinetic (PK) studies of daptomycin have been reported in infants <120 days of age with suspected Gram-positive infection 7 and in pediatric patients 2-17 years of age with proven or suspected Gram-positive infection, 8,9 but not in infants 3-24 months of age. 3,5,6 Pharmacokinetic (PK) studies of daptomycin have been reported in infants <120 days of age with suspected Gram-positive infection 7 and in pediatric patients 2-17 years of age with proven or suspected Gram-positive infection, 8,9 but not in infants 3-24 months of age.…”
mentioning
confidence: 99%
“…Therefore, persistent bacterial growth at the end of 5 days of vancomycin therapy poses a need for a potent antimicrobial with enhanced activity against MR-CoNS. Although the use of daptomycin is restricted in neonates, it has shown a good cure rate in several studies [ 22 , 23 ]. Our study included a case series of 21 newborns with Staphylococci infections, and we found that daptomycin intervention provided successful recovery in around 62% of the patients.…”
Section: Discussionmentioning
confidence: 99%